'The Museum of Today': Harald Szeemann's Science Fiction. (1st April 2018) - Muller, Lizzie
Harald Szeemann's 1967 exhibition Science Fiction is ripe for re-examination. Insights gained from unpublished handwritten notes reveal Szeemann's endless listmaking as a connective curatorial methodology that sought to re-create an expansive science fiction 'state of mind'. The resulting exhibition of over 3, 000 diverse objects stands in contrast to the sterile space-age aesthetics of the white cube that was, at the same moment, becoming the pre-eminent form of contemporary art display. The popular response to Science Fiction stimulated Szeemann to conceptualize a 'Museum of Today' that would dynamically reflect its moment in time – a concept that resonates in Szeemann's subsequent work and in contemporary curatorial practice.